Danantara Indonesia and investment policy disorientation - Handoko, Aloysius Dewanto; Sirait, Ningrum Natasya; Siregar, Mahmul; Nasution, Mirza (Edelweiss Applied Science and Technology, 2025)
Investment is the backbone of economic growth. Unfortunately, the Indonesian government has never implemented appropriate regulations to promote investment as a strategy for achieving public welfare. This research employed a normative legal research method involving the examination of various documents based on secondary data sources. Data was obtained through a literature study of legal source materials consisting of primary and secondary legal materials. This research takes a prescriptive approach by addressing legal issues arising from the lack of consideration for the interests of the general public, who have not yet achieved prosperity, proposing that these interests serve as a paradigm in formulating all economic regulations, particularly in the investment sector. Due to this absence, the government faces disorientation in its efforts to promote public welfare. Therefore, recommendations are proposed as strategic solutions to initiate reforms in investment law, ensuring a more equitable framework that benefits all segments of society and supports the advancement of general welfare. This article inquires whether the establishment of Badan Pengelola Investasi Daya Anagata Nusantara or Danantara Indonesia by the government is the right step to encourage investment in order to advance public welfare. Using normative legal research methods, the research findings show that regulations pertaining to investment in Indonesia only favor the interests of large-scale businesses (corporations), thus ignoring the interests of the wider community. For this reason, it is recommended that the government carry out fundamental legal reforms to various regulations in the field of investment to realize public welfare.